2015
DOI: 10.1016/j.bcp.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic mapping of A3 adenosine receptor agonist MRS5980

Abstract: (1S,2R,3S,4R,5S)-4-(2-((5-Chlorothiophen-2-yl)ethynyl)-6-(methylamino)-9H-purin-9-yl)-2,3-dihydroxy-N-methylbicyclo[3.1.0]hexane-1-carboxamide (MRS5980) is an A3AR selective agonist containing multiple receptor affinity- and selectivity-enhancing modifications and a therapeutic candidate drug for many inflammatory diseases. Metabolism-related poor pharmacokinetic behavior and toxicities are a major reason of drug R&D failure. Metabolomics with UPLC-MS was employed to profile the metabolism of MRS5980 and MRS59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…C2‐triazole substitution (two positional isomers) was previously found to be compatible with A 3 AR binding in the riboside series, as in 15a and 15b . As a postscript to that effort to replace the C2‐arylethynyl group, this ethynyl group was found to be relatively unreactive toward thiols such as glutathione, and the risk of such compounds depleting liver glutathione was shown to be very small …”
Section: Medicinal Chemistry Of the A3 Adenosine Receptormentioning
confidence: 93%
See 1 more Smart Citation
“…C2‐triazole substitution (two positional isomers) was previously found to be compatible with A 3 AR binding in the riboside series, as in 15a and 15b . As a postscript to that effort to replace the C2‐arylethynyl group, this ethynyl group was found to be relatively unreactive toward thiols such as glutathione, and the risk of such compounds depleting liver glutathione was shown to be very small …”
Section: Medicinal Chemistry Of the A3 Adenosine Receptormentioning
confidence: 93%
“…132 As a postscript to that effort to replace the C2-arylethynyl group, this ethynyl group was found to be relatively unreactive toward thiols such as glutathione, and the risk of such compounds depleting liver glutathione was shown to be very small. 133 The surprising finding that substitution of the exocylic NH of adenine with H or CH 3 in MRS5919 32 allowed full activation of the A 3 AR emphasized that the loss of otherwise important recognition elements in a ligand can be compensated by other affinity enhancing moieties on the nucleoside. 134 Moreover, the ribose moiety is the main effector of receptor activation, while adenine modifications tend to change the subtype selectivity but usually do not have a major effect on the agonist efficacy.…”
Section: Adenosine Derivatives As Agonists Of the A 3 Adenosine Receptormentioning
confidence: 99%
“…Drug metabolism is significant in explaining and predicting efficacy and toxicity [11]. The metabolic profile of drugs and drug candidates can be clearly elucidated through combining in vitro incubation mixtures and in vivo animal models [12]. The pharmacokinetics of the six bioactive lignans in WZ were also measured and we found that most of…”
mentioning
confidence: 93%
“…Furthermore, our previous studies reveal that WZ and its active lignans significantly protect against liver injury including acetaminophen-induced liver injury [7,8], partial hepatectomy [9] and lithocholic acid-induced cholestasis [10].Drug metabolism is significant in explaining and predicting efficacy and toxicity [11]. The metabolic profile of drugs and drug candidates can be clearly elucidated through combining in vitro incubation mixtures and in vivo animal models [12]. The pharmacokinetics of the six bioactive lignans in WZ were also measured and we found that most of…”
mentioning
confidence: 99%
“…MRS5980 37 is a highly selective C2-arylethynyl (N)-methanocarba A 3 AR agonist, which has been demonstrated to be highly efficacious in in vivo pain models following administered by oral gavage, with a protective effect lasting up to 3 h (Tosh et al, 2014; Janes et al, 2016), and its metabolomics has been studied (Fang et al, 2015). The 2-chlorothienyl group is stable in vivo , and the aryl alkyne group was shown to be not highly reactive.…”
Section: Ar Agonists For Clinical Developmentmentioning
confidence: 99%